Computational modelling of light-matter interaction in aSi with CdSe/ZnS core/shell quantum dots and metal nanoantenna for solar cell applications - Basyir Rodhuan, Mirza; Abdul-Kahar, Rosmila; Ameruddin, Amira Saryati; Mohd Rus, Anika Zafiah; Kim Gaik Tay, Kim Gaik Tay (2023)
As the world population rises, energy needs are become critical. Using photovoltaic technologies like amorphous silicon solar cells(aSiSC)to harvest solar power might benefit global concern. Previous research claimed that aSiSCs were modest short-wavelength absorbers. Quantum dot(QD) may be applied to the aSiSC to enhance optical absorptions and electric fields as the QD’s bandgap is tunable, which can cover a broader electromagnetic range. This study aims are to design the 3D aSiSC with QD on the model and to investigate the optical absorption peak, electric field profiles, and light–matter interaction of the models via COMSOL Multiphysics software. From the base model, the optical absorption improved from 736 nm at 41.827% to 46.005% at 642 nm for the aSiQDSC model which developed with 0.5/3.0 nm radius of core/shell cadmium selenide/zinc sulphide (CdSe/ZnS). This study proceeded combining rectangular nanosheets gold and silver nanoantenna (Au and Ag NA) with various gap g of NA to the aSiQDSC models where g = 0.5 nm Ag NA model was presented the higher optical absorption of 47.246% at 650 nm, and electric fields of 2.53 × 1010 V nm−1 Computationally, this ultimate design is ecologically sound for solar cell applications, which allow future direction in renewable energy research and fabrication